TUBERCULOUS ADRENAL ABSCESS ASSOCIATED WITH TUBERCULOSIS OF THE LUNGS AND BRAIN: A CASE REPORT - SUNGTONG, Phuvitoo (The ASEAN Journal of Radiology, 2023)
Tuberculous adrenal abscess was diagnosed in a 46-year-old man who presented with fever, abdominal pain, and weight loss. Ultrasonography revealed a well-marginated right suprarenal mass with internal hypoechoic areas. By CT scan, it showed thin rim enhancement with multiple septal enhancement and central hypodense areas. Tuberculous adrenal abscess was diagnosed by isolation of tuberculous bacilli from the lesion under CT guidance. He also had evidence of miliary pulmonary tuberculosis from chest radiograph and intracranial tuberculosis from CT scan of the brain.